Fusarium blight of common buckwheat in Primorsky krai - N. V. Matsishina; S. A. Borovaya (Овощи России, 2022)
Relevance. Common buckwheat is one of the most important cereal and melliferous crops being in demand both in Russia and overseas. Despite the fact that buckwheat has lower sus- ceptibility to infectious diseases in comparisons with other grain and cereal crops, research on its pathogens is a topical issue considering a high disease rate for this crop in Primorsky krai. Materials and methods. The study on pathogenic composition was conducted in selective crop rotations of FSBSI “FSC of Agricultural Biotechnology of the Far East named after A.K. Chaiki” at the territory of Ussuriysky district in Primorsky krai. Indeterminate (Izumrud, Pri 7, Bashkirskaya krasnostebel’naya) and determinate (Dikul) buckwheat varieties were used for the study. Fungi were isolated from rhizoplane using water washing technique, from soil and rhizosphere via the dilution method, from leaves and root systems by accumulation in a moist chamber with subsequent transfer of culture onto selective medium. Fungal isolates were cul- tivated on toxigenic medium (Myro) to determine their phytotoxicity. Phytopathogenic activity of living cultures was evaluated on potato sucrose agar according to the modified method of Chelkowski and Manka . All experiments were conducted in accordance with established methods.Results. Culture filtrates of F. avenaceum and F. graminearum isolates, obtained from different anatomical parts of common buckwheat, were characterized by low toxicity, and culture filtrates of F. oxysporum isolate were highly toxic. Phytotoxicity of pathogens manifested itself not only in decrease in laboratory germination ability of buckwheat seeds, but also in inhibition of buckwheat sprout development. It proved that metabolites exerted a prolonged effect on sensitive plants. F.avenaceum, F. oxysporum and F. graminearum have pronounced phy- topathogenic and aggressive properties in relation to buckwheat and test-plants in the laboratory conditions. The sum total of their studied phytotoxic properties is convincing enough to consider them potentially hazardous to buckwheat for wilt disease development.